Nitrogen and Potassium Fertilization in a Guava Orchard Evaluated for Five Cycles: Soil Cationic Balance - Montes, Rafael Marangoni [UNESP]; Parent, Leon Etienne; Amorim, Daniel Angelucci de; Rozane, Danilo Eduardo [UNESP]; Parent, Sergie-Etienne; Natale, William; Modesto, Viviane Cristina [UNESP] (Soc Brasileira De Ciencia Do Solo, 2016)
Soil fertility evaluation through soil analysis traditionally does not consider interaction among elements. To include the interaction effect in interpretation of soil analyses, an experiment was conducted to evaluate the effect of nitrogen fertilization (0, 0.5, 1.0, and 2.0 kg N per plant per cycle) with urea (45 % N) and potassium fertilization (0, 0.55, 1.1, and 2.2 kg K2O per plant per cycle) with potassium chloride (60 % K2O) on soil cationic balance. The experiment was carried out in an irrigated commercial production area of 'Paluma' guava, for five consecutive cycles, 2009 through 2012, using the concept of isometric log ratio (ilr) to evaluate soil cationic balance through [K, Ca, Mg | H+ Al], [K | Ca, Mg] and [Ca | Mg] balances. The compositional data analysis showed to be a suitable tool to interpret the soil cationic balance given that the soil cationic balances value was changed by nitrogen fertilization and potassium as well as the soil pH value and the concentration of K in the soil. The soil cationic balances also changed by the variations of in climate conditions at period of soil sample. An application rate of 0.55 kg K2O per plant per cycle was considered sufficient to keep K soil concentration above 1.6 mmol(c) dm(-3).
Keywords: compositional analysis of data; isometric log ratio (ilr); Psidium guajava L